واقع تدريس اللغات الأجنبية واللغة الوطنية في التعليم قبل الجامعي: عرض تجارب - الكثيري, عامر; التاجوري, نعيمة (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
This study aims to compare different educational systems in the field of teaching foreign languages in the pre-university stages of study by presenting the experiences of three different countries: the experience of the Sultanate of Oman in the Middle East, the experience of Libya in North Africa, and the experience of France in Europe. The importance of the study lies in knowing the strengths and weaknesses of each experience and trying to benefit from France’s experience in the field of harmonization between its national language and foreign languages. The material for this study was collected from articles, books, and publications from the ministries of education in each country separately, and then compared. The data showed that in all of these countries, students are exposed to the English language, as it is considered the second language after the official national language, with students’ exposure to this language varying between private schools and government schools. The situation in Libya is also more turbulent in adopting foreign languages, which is a turmoil due to general unrest on the political side. تهدف هذه الدراسة إلى المقارنة بين نظم تعليمية مختلفة في مجال تدريس اللغات الأجنبية في مراحل الدراسة قبل الجامعية من خلال عرض تجارب ثلاث دول مختلفة، هي: تجربة سلطنة عمان في الشرق الأوسط، وتجربة ليبيا في شمال إفريقيا، وتجربة فرنسا في أوروبا؛ وتكمن أهمية الدراسة في معرفة مكامن القوة والضعف في كل تجربة ومحاولة الاستفادة من تجربة فرنسا في مجال المواءمة بين لغتها الوطنية واللغات الأجنبية. وجمعت مادة هذه الدراسة من المقالات والكتب والمطبوعات الخاصة بوزارات التعليم في كل بلد على حدّة ثم مقارنتها. وأظهرت البيانات أن كل هذه الدول يتعرض فيها الطلبة للغة الإنجليزية بعدّها اللغة الثانية بعد اللغة الوطنية الرسمية مع تفاوت تعرض الطلبة لهذه اللغة بين المدراس الخاصة والمدارس الحكومية، كما أن الوضع في ليبيا أكثر اضطرابا في اعتماد اللغات الأجنبية وهو اضطراب راجع إلى اضطرابات عامة في الجانب السياسي.